Implementing Total Quality Management (TQM) to Enhance the Quality of Islamic Education: A Library Research Study - Aini, Qurrotul; Julaiha , Siti (Journal of Educational Management Research, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) to enhance the quality of Islamic Education using a library research approach. By reviewing accredited journals, books, proceedings, and relevant documents, TQM is explored as a strategic approach to improving Islamic Education effectiveness through principles of continuous improvement, customer focus (students), process strengthening, and human resource empowerment. The findings indicate that TQM implementation positively impacts the quality of Islamic Education, teacher professionalism, classroom management, and the development of students' religious character. The study also identifies supporting factors such as Leadership commitment, a quality culture, and data-driven evaluation systems. At the same time, challenges include a limited understanding of TQM concepts and the lack of measurable quality standards for Islamic Education. Literature synthesis emphasizes that integrating TQM into Islamic Education has significant potential to comprehensively enhance Islamic education when applied consistently, collaboratively, and contextually. This research is expected to serve as a conceptual reference for educational institutions in developing TQM-based quality strategies for Islamic Education.